Entrando na partida: a formulação de políticas de comunicação e cultura para jogos digitais no Brasil entre 2003 e 2014 - Zambon, Pedro Santoro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research aims to describe how was the process for the formulation of public policies concerning the communication and culture for the digital games in Brazil, along the first twelve (12) years of PT (Workers Party) government. The trajectory of games as an object of public policies has been established - starting from their origin of those policies in software related ones, including their treatment a cultural policy, to finally include them in the category of communication policy content. The political processes that supported such transition from a systemic agenda for the government has been identified, followed by a process of mapping and systematization of laws, projects, tenders, comissions and government programs, in a federal level. Starding from the policies cycle, it has been observed the formulation stage - which includes the decision-making process - under the perspective of the incrementalist model, from Lindblom (1959). Understanding the adjustment of interests centrally, the role of both state actors and stakeholding groups in the formulation, the decision-making arenas has been seen as a way to identify them. Complementing those processes with interpretations of interviews that sometimes reveal information which is not presented in official documents and media, policies formulated by the government actors were characterized according to the typology of Wilson (1983), identifying costs and benefits among different sectors in the string value of digital games. The application of this typology has enabled us to realize that in addition to initiatives being that have been developed incrementally, based on devices and policies of other sectors, stakeholding groups have demonstrated an active role in decision making, and the chain industry most benefited in the development cycle

Esta pesquista tem como objetivo descrever de que forma se deu o processo de formulação das políticas de comunicação e cultura para jogos digitais no Brasil nos primeiros 12 (doze) anos de governo do PT (Partido dos Trabalhadores). Foi estabelecida a trajetória dos games enquanto objeto de políticas públicas - partindo de sua origem nas políticas software, passando pelo tratamento enquanto política cultural até a inclusão como política de comunicação para conteúdos. Os processos políticos que subsidiaram a transição de uma agenda sistêmica para a governamental foram identificados, seguidos por mapeamento e sistematização das leis, projetos, editais, comissões e programas governamentais em âmbito federal. Partindo do ciclde políticas, foi observada a etapa de formulação - a qual se inclui o processo de tomada de decisão - sob ótica do modelo incrementalsta de Lindblom (1959). Entendendo a centralidade do ajuste mútuo de interesses e o papel dos atores governamentais e grupos de interesse na formulação, foram observadas as arenas decisórias como meio de identifica-los. Complementando com entrevistas interpretativas as informações não dispostas em documentos oficiais e mídia, as políticas formuladas pelos atores governamentais foram caracterizados segundo a tipologia de Wilson (1983), identificando os custos e benefícios entre os diversos setores da cadeia de valor de jogos digitais. A aplicação dessa tipologia nos permitiram perceber que, além das iniciativas serem desenvolvidas incrementalmente com base em dispositivos e políticas de outros setores, os grupos de interesse demonstram ter um papel atuante na tomada de decisão, sendo o setor da cadeia mais beneficiado no período o de desenvolvimento
Keywords: Jogos eletronicos; Políticas públicas; Politica de comunicação; Politica cultural; Mídia digital; Sociedade digital; Electronic games